Hacker's Delight - Warren, Henry (Addison-Wesley Professional, 2002)
"This is the first book that promises to tell the deep, dark secrets of computer arithmetic, and it delivers in spades. It contains every trick I knew plus many, many more. A godsend for library developers, compiler writers, and lovers of elegant hacks, it deserves a spot on your shelf right next to Knuth."--Josh Bloch "When I first saw the title, I figured that the book must be either a cookbook for breaking into computers (unlikely) or some sort of compendium of little programming tricks. It's the latter, but it's thorough, almost encyclopedic, in its coverage." --Guy Steele These are the timesaving techniques relished by computer hackers--those devoted and persistent code developers who seek elegant and efficient ways to build better software. The truth is that much of the computer programmer's job involves a healthy mix of arithmetic and logic. In Hacker's Delight, veteran programmer Hank Warren shares the tricks he has collected from his considerable experience in the worlds of application and system programming. Most of these techniques are eminently practical, but a few are included just because they are interesting and unexpected. The resulting work is an irresistible collection that will help even the most seasoned programmers better their craft. Topics covered include: A broad collection of useful programming tricks Small algorithms for common tasks Power-of-2 boundaries and bounds checking Rearranging bits and bytes Integer division and division by constants Some elementary functions on integers Gray code Hilbert's space-filling curve And even formulas for prime numbers! This book is for anyone who wants to create efficient code. Hacker's Delight will help you learn to program at a higher level--well beyond what is generally taught in schools and training courses--and will advance you substantially further than is possible through ordinary self-study alone. 0201914654B06272002.